The Challenges and Prospects of Science Education Development in Africa - Ayeni, Margaret Foluso (Richtmann Publishing, 2021)
In spite of the numerous groundbreaking innovations and inventions that science education can achieve in Africa, its growth in the continent is stunted. This retardation in development is as a result of fundamental problems which are discussed in the paper under the following headings: Insecurity, corruption, Unavailability of Laboratory Equipment and Instructional materials, Inadequate Funds, Inadequate Teacher Quality and Teaching Method, Difficult concepts in science. The paper highlights the challenges crippling the development of science education and the prospects its growth will have in the growth of Africa as a continent. Also, this paper focuses on the challenges plaguing science education in African Countries. It intends to reveal how science education is being prevented from becoming prominent in the national and sustainable development of African countries. It also discusses the prospects science education will have in the development of the continent if it was not plagued with difficulties. Some recommendations were made on the steps to take to improve the development of science education in Africa. Â Received: 4 April 2021 / Accepted: 28 June 2021 / Published: 8 July 2021